Investigation of Different Miniscrew Head Designs by Finite Element Analysis - GÖKÇE KARA, GÖKÇENUR (My University, 2024)
Objective: To determine the optimum miniscrew head design in orthodontic treatments for primary stability and compare stress distribution on a representative bone structure. Methods: Miniscrews with cross heads, mushroom-shaped heads, button heads, bracket heads, and through-hole heads were compared using finite element analysis. Miniscrews, whose three-dimensional drawings were completed using the SolidWorks computer-aided software package, were inserted in the bone block. Orthodontic force was applied to the head, and stress distributions, strains, and total deformations were investigated. Results: The lowest von Mises stress of 5.67 MPa was obtained using the bracket head. On the other hand, the highest von Mises stress of 22.4 MPa was found with the button head. Through mesh convergence analysis, the most appropriate mesh size was determined to be 0.5 mm; approximately 230,000 elements were formed for each model. Conclusion: Because the need for low stress is substantial for the primary stability of the miniscrew, this study demonstrated that the bracket head miniscrew is the optimal head design. In addition, it is posited that the success rate of orthodontic anchorage treatments will increase when bracket head miniscrews are used. Keywords: Miniscrew, temporary anchorage, orthodontic treatment, finite element analysis
Keywords: Miniscrew; temporary anchorage; orthodontic treatment; finite element analysis